STUDI FAKTOR-FAKTOR YANG MEMPENGARUHI WANITA BEKERJA DI KOTA DENPASAR - Desak Putu Eka Nilakusmawati; Made Susilawati (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2012)
This study aims to investigate the influencing factors of married women to involve into job market. This research used approach of survey, by using enquette as data compiler. Responder in this research is wife with husband have job, conducted by purposive sampling. Total of responden to be taken 131 responden. The variables of this research are: woman do not work or work (Y), education level of wife (X1), amount of total expenditure of family (X2), amount of husband’s income (X3), number of depending family (X4), and type of main occupation of husband (X5). The analysis techniques used descriptive analysis and log-linear analysis. The results using the log-linear analysis showed that the most influence factor on woman to work is education level of wife and amount of husband’s income, while other variables such as amount of total expenditure of family, number of depending family, and type of main occupation of husband, also affect but by indirectly.